1052. Do Healthcare Providers De-Escalate β-Lactam (BL) Antibiotic Therapy Based on Results of Antibiotic Susceptibility Testing (AST)? Analysis of Bloodstream Infections (BSI) Caused by Escherichia coli and Klebsiella pneumoniae From the Veterans Health Administration (VHA). (26th November 2018) - Viau, Roberto; Wilson, Brigid; Evans, Scott R; Perez, Federico; Fowler, Vance G; Chambers, Henry F; Kreiswirth, Barry N; Patel, Robin; Banerjee, Ritu; Bonomo, Robert A; ,
Abstract: Background: Achieving appropriate therapy for BSI caused by Gram-negative rods (GNR) is challenging. The availability of AST results allows de-escalation from broad- to narrow-spectrum agents. De-escalation is a goal of antimicrobial stewardship (AS). Through the analysis of inpatient BL antibiotic regimens in a nationwide cohort of patients with Escherichia coli and Klebsiella pneumoniae BSI, we compared the relative spectrum of empiric and definitive treatments to AST results and identified opportunities for de-escalation. Methods: Using a cohort of patients hospitalized within VHA, we identified patients with a blood culture positive for E. coli or K. pneumoniae between 2006 and 2015. We analyzed the subset of patients receiving inpatient BLs before and after Gram stain (GS) and AST results. BLs were grouped into five tiers of increasing spectrum, both with and without a requirement for anaerobic activity (Figure 1). Tiers of BLs across the treatment periods were summarized and compared with the lowest-spectrum tier with an active agent. Rates of inactive, optimal, and overly broad BL therapy were summarized by organism and treatment period. Results: Of 36, 531 BSI identified, we analyzed a subset of 10, 825 (7, 100 E. coli, 3, 725 K. pneumoniae ) that met our inclusion criteria (Figure 2). The use of inactive BL agents decreased across time, falling from 11% in early empiric to 4.5% in definitive treatments. The proportion of patients receiving the narrowest available effective BL therapy ("optimal" therapy) increased from 5% to 8% after GS results and to 14% after AST results (Figure 3). De-escalation to optimal therapy after AST results was observed in only 7% of opportunities. If anaerobic activity was required, a smaller proportion of cases would be considered overtreated in the empiric periods (45–46%), but de-escalation after AST results was observed in only 10% of these cases. Conclusion: Changes in BL agents across treatment periods reflect an escalation to active treatment, but the absence of de-escalation after AST results was available. This was true both with and without considering a need for anaerobic activity. Expansion of this analysis to include additional classes such as fluoroquinolones may reveal opportunities for AS and de-escalation to optimal therapy in the treatment of E. coli and K. pneumoniae BSI. Disclosures: R. Patel, CD Diagnostics, BioFire, Curetis, Merck, Hutchison Biofilm Medical Solutions, Accelerate Diagnostics, Allergan, and The Medicines Company: Grant Investigator, Research grant – monies paid to Mayo Clinic. Curetis, Specific Technologies, Selux Dx, GenMark Diagnostics, PathoQuest and Genentech: Consultant and Scientific Advisor, Consulting fee – monies paid to Mayo Clinic. ASM and IDSA: Travel reimbursement and editor's stipends, Travel reimbursement and editor's stipends. NBME, Up-to-Date and the Infectious Diseases Board Review Course: Varies, Honoraria. Mayo Clinic: Employee, Salary. R. Banerjee, Accelerate Diagnostics, Biomerieux, BioFire: Grant Investigator, Research grant and Research support.